An MCNP simulation study of an oil well logging benchmarking tool and a test enclosure - Pinilla, Maria Isabel (Kansas State University, 2019)
The research contained within outlines a series of simulation studies conducted to design an oil well logging tool and a testing enclosure that will be used to benchmark a Monte Carlo- Library Least Squares (MCLLS) code, currently under development at North Carolina State University. Computer simulations were conducted to aid in the design of the benchmarking tool, as well as a test enclosure to be used as an infinite medium where measurements were to take place. An initial tool configuration was modeled in MCNP6® to perform simulations while varying design parameters to learn about the behavior of the tool. Shielding and effectively infinite medium studies were conducted in order to optimize the tool geometry and experiment design. A deuterium-tritium (D-T) generator, which produces up to 1.6×10⁸ neutrons per second, will be used as a source to replace the Am-Be and cesium-137 sources typically found in well logging tools. Helium-3 and NaI(Tl) detectors will be used to measure the γ-ray and neutron spectra when different materials such as water, sand, and limestone surround the tool. The MCLLS code being developed could lead to new computer algorithms that take advantage of inelastic-scatter γ-rays generated by high-energy neutrons in the surrounding material to determine the composition of the formation.
Keywords: Monte Carlo; Simulation; Radiation